The Relationship Between Fine Motor Skills and Social Development and Maturation - Leila Dehghan; Navid Mirzakhani; Mehdi Rezaee; Mehdi Tabatabaee (Iranian Rehabilitation Journal, 2017)
Objectives: Social development in children is influenced by several factors, including family, school friends, television, gender, race, socioeconomic status, and locomotor activity, and depending on the situation and how they react to it, social development and maturity might get accelerated or get undermined. Therefore, in this study, we aimed to investigate the relationship between fine motor skills and social development and maturity in children. Methods: This is a descriptive-analytical study that included 85 children in the age group of 6-8 years (41 boys and 44 girls). We used a two-stage random sampling method in order to select samples from elementary schools in Regions 14 and 15, Tehran. Information was collected through the General Health Questionnaire and demographic questionnaire, which was filled by the parents. Fine motor skills test consisting of three subtests, i.e., response speed, visual-motor control, and upper-limb speed and dexterity, was measured using Bruninks-Oseretsky Test of Motor Proficiency. Social maturity was measured using Vineland social maturity scale. The entire process lasted for a month and the mean, standard deviation, range of changes, minimum, and maximum values were analyzed. Mann-Whitney test was used to compare mean scores of variables between male and female groups and significance level for statistical tests was analyzed at α=0.05. Results: Significant correlation between social quotient and total score of fine motor skills variable was obtained (P<0.001, r=0.46). A significant correlation was also observed between visual-motor control score and social quotient (P<0.001, r=0.44) and between social quotient and upper-limb speed and dexterity (P<0.001, r=0.36). However, there was no significant correlation observed between response speed and social quotient (P<0.42, r=0.08). Discussion: According to the results, there is a significant association between fine motor skills with respect to visual-motor skills of hands and social competence and maturity in children, and it can be used as impact factor for to improve in children’s social growth.